Analytical design and implementation of a sequential display signboard - O. Daniel , T.; Ochola, D.; O. Edaogbogun , G.; K. Olawale , O.; E. Okobi , P. (International Journal of Physical Research, 2024)
This study is aimed at the analytical design of a lighting system called a sequential display signboard to create a special illumination effect, which can be used in cock tail, disco halls, offices door, theatre and signboards using relevant mathematical equations and physics relations. The sequential display signboard consists of power supply unit connected to an arrangement of oscillator and switching circuits that triggered the light emitting diodes (LED) to display the words which are written inform of a message display. The system consists of 555 timers which functions as an Astable Multivibrator to generate pulses and transistors acting as switches thereby aiding the display of the message. With an input pulse from the 555 timer, the 4017 IC will cycle through its ten count sequence, lighting up each LED one at a time and recycling back to the first LED which results in a visual pleasing sequence of flashing lights in form of a message display.